2006
DOI: 10.2165/00003088-200645040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Biowaiver Extension to Biopharmaceutics Classification System Class III Drug Products

Abstract: The results of the present study indicated that the absorption of cimetidine from IR tablets is, in general, limited by permeability rather than dissolution. IVIVC analysis demonstrated that only when the release was deliberately retarded (tablets containing 26% methacrylate copolymer), did the dissolution represent the rate-limiting step to drug absorption. On the in vitro side, it seems that 85% dissolution within 30 minutes, as currently required by the US FDA Guidance, is more than sufficient to guarantee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 23 publications
5
65
0
1
Order By: Relevance
“…According to the Biopharmaceutics Classification System, piroxicam is classified as a class II drug exhibiting low solubility and high permeability (10,11). Cimetidine is assigned as a class III drug (10,12), a drug with high solubility and poor permeability. A combination of these two drugs may lead changes in the dissolution profile of piroxicam.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Biopharmaceutics Classification System, piroxicam is classified as a class II drug exhibiting low solubility and high permeability (10,11). Cimetidine is assigned as a class III drug (10,12), a drug with high solubility and poor permeability. A combination of these two drugs may lead changes in the dissolution profile of piroxicam.…”
Section: Introductionmentioning
confidence: 99%
“…5 shows the regression analysis data. The IVIVC did not show a characteristic linear distribution of its dosage form either in the modified or immediate release of class II drugs (reference), instead an inverted L-shaped distribution was obtained which has been observed by others (45). This indicated that the method utilized for the dissolution study of the efavirenz tablets resulted in a fast dissolution of the drug.…”
Section: In Silico Studiesmentioning
confidence: 61%
“…A bioavailability study in a patient with a massive bowel restriction demonstrated reduced absorption of cimetidine which was attributed to rapid transit of drug through the GIT tract 45 . Both the absorption and clearance of cimetidine are linear in the therapeutic range 19,46 . Using the everted d ring technique the uptake of cimetidine from the rat jejunum and colon was show to be linear in the range 0.005-40 nM 47. After oral administration in the fasted state cimetidine usually show erratic double peak or multiple peak phenomenon in plasma drug concentration-time profile 19,44,48 . The phenomenon has been described extensively and still under discussion.…”
Section: 43mentioning
confidence: 99%